Evolution and revolution in China's skill formation system - Xu, Jing [Verfasser] (My University, 2011)
"This article outlines the current problems facing vocational education in China in order to raise the question as to how deep-seated and intractable they might be. In order to address this question a historical analysis of vocational education from the turn of the twentieth century to the end of Mao's period of office is undertaken. The rise of vocational education at school did not take place in China until 1905. Its successive development was pursued simply in a pragmatic way. It suggests that the impact of regular academic schooling on setting standards both for learning and for subsequent employment opportunities should not be underestimated. It argues that the preference for higher and formal education endangered what was seen as the lower level of vocational and informal adult education, which undermined China's skill formation system. In the light of this historical analysis, consideration is given to the prospects for the development of vocational and adult education in China today." (Autorenreferat, BIBB-Doku)
Keywords: Berufsbildungssystem; Berufsbildung; Erwachsenenbildung; Kompetenzentwicklung; Historische Entwicklung; Fachkräftebedarf; Zukunftsperspektive; China